2018
DOI: 10.1016/j.cgh.2017.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Costs Associated With Eosinophilic Esophagitis: A Systematic Review

Abstract: EoE negatively impacts the HRQoL of patients and their families, and is a burden to the health care system. Although data are sparse, currently available treatments appear to improve HRQoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(71 citation statements)
references
References 26 publications
1
65
0
5
Order By: Relevance
“…According to Australian census data (46), it would mean that the survey captured between 4 and 40% of the pediatric EoE population in Australia, depending on what would be considered as accurate prevalence data at the time. A 2018 systematic review and meta-analysis (47), which included 13 studies, focused on HRQoL in patients with EoE of all ages. The sample sizes ranged from n = 8 (Australia) (48) to n = 140 (USA) (49), emphasizing the large sample size of the study reported here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Australian census data (46), it would mean that the survey captured between 4 and 40% of the pediatric EoE population in Australia, depending on what would be considered as accurate prevalence data at the time. A 2018 systematic review and meta-analysis (47), which included 13 studies, focused on HRQoL in patients with EoE of all ages. The sample sizes ranged from n = 8 (Australia) (48) to n = 140 (USA) (49), emphasizing the large sample size of the study reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that nearly two-thirds of the children did not have a healthcare card and a third of the respondents did not have private health insurance to reduce out-of-pocket expenses. Further exploration of financial burden is needed as existing data indicate that EoE-related costs are striking and consistently higher than those of healthy consumers (10,47). The economic impact of poorly coordinated care encompassing the possible duplication of services as parents attempt to meet the healthcare needs of their family must be carefully considered.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 20 years, eosinophilic esophagitis (EoE) has emerged as a significant cause of upper gastrointestinal (GI) morbidity, with significant quality of life implications for patients ( Straumann and Simon, 2005 ; Hruz et al, 2011 ; Cianferoni and Spergel, 2016 ; Cianferoni et al, 2015 ; Mukkada et al, 2017 ) and an estimated $1.4 billion annual healthcare cost ( Jensen et al, 2015 ). This disorder can affect both children and adults, with symptoms that vary by age, but typically include difficulty eating, failure to thrive, dysphagia and food impaction.…”
Section: Introductionmentioning
confidence: 99%
“…2 Patients with EoE experience dysphagia, food impaction, and disease anxiety, which significantly affect quality of life of patients and their families. 3 The diagnosis of EoE is established by clinical symptoms of esophageal dysfunction and esophageal eosinophilia 15 eosinophils per high-power field (eos/hpf). 4 Therefore, both initial diagnosis and histologic response to therapy can only be made through pathologic assessment of endoscopic biopsies.…”
mentioning
confidence: 99%